Two mechanisms of cardiac stem cell-mediated cardiomyogenesis in the adult mammalian heart include formation of colonies and cell-in-cell structures - Belostotskaya, Galina B. (Oncotarget, 2018)
AIMS: Because the mechanism of mature cardiomyocyte (CM) development from cardiac stem cells (CSCs) is not fully understood, we explored the involvement of CSCs into two pathways of cardiomyogenesis in adult mammalian heart: (1) via colony formation and (2) by means of intracellular development of CSCs inside CMs followed by the formation of “cell-in-cell structures” (CICSs). METHODS AND RESULTS: Using immunostaining and confocal microscopy, we studied the presence of CSC-derived colonies, CICSs and transitory amplifying cells (TACs), released from ruptured CICSs, in a suspension of ex vivo freshly isolated myocardial cells of mammals of different age and species, human including. All subsets of CSCs (c-kit+, Sca-1+ and Isl-1+) were found in mammals of different age. It was shown that c-kit+ and Sca-1+ CSCs produce both colonies and CICSs. However, Isl-1+ CSCs seem to be involved in cardiac growth during first month of age only both through colony formation and CICS generation. In turn, the studies on myocardial cell suspensions of adult C57/bl6N mice, one-year-old bull and 45-year-old woman not only confirmed the involvement of c-kit+ and Sca-1+ CSCs in both mechanisms of cardiomyogenesis, but also showed that Isl-1+ colonies are present in the myocardium of adult mice and rarely in human. CONCLUSIONS: The presence of CSC-derived colonies, CICSs and TACs in all experimental specimens of myocardium proved our previous hypothesis about two pathways that generate new CMs in adult heart. Moreover, we suggest that TACs play a central role in self-renewal of myocardium throughout the lifetime of mammals.